2022
DOI: 10.3389/fpubh.2022.907222
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Acute Postoperative Pain After Open Radical Gastrectomy for Gastric Cancer

Abstract: BackgroundPain has become an important factor in evaluating patients' quality of life and clinical treatment. For gastric cancer (GC) patients, open radical gastrectomy (OG) causes significant trauma to the body, increases patients' pain after operation, and delays early recovery. The aim of this study was to investigate the predictive factors of acute pain after OG within postoperative 72 h.MethodsFrom March 2020 to September 2021, 307 patients who underwent OG were included in the study in Nanjing Drum Tower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Prospective and retrospective cohort studies have revealed that ALND is among the independent predictors of moderate-to-severe acute pain following breast cancer surgery. 22,38,72 Additionally, this surgical approach exhibited an independent association with APSP among other surgery types, such as inguinal hernia repair, 62 cesarean section, 69 open radical gastrectomy, 56 and endoscopic sinus surgery. 63 Postoperative pain is generally accepted to be more severe in patients undergoing major surgeries or surgeries with more extensive nerve damage.…”
Section: Types Of Surgery and Surgical Approachesmentioning
confidence: 91%
See 1 more Smart Citation
“…Prospective and retrospective cohort studies have revealed that ALND is among the independent predictors of moderate-to-severe acute pain following breast cancer surgery. 22,38,72 Additionally, this surgical approach exhibited an independent association with APSP among other surgery types, such as inguinal hernia repair, 62 cesarean section, 69 open radical gastrectomy, 56 and endoscopic sinus surgery. 63 Postoperative pain is generally accepted to be more severe in patients undergoing major surgeries or surgeries with more extensive nerve damage.…”
Section: Types Of Surgery and Surgical Approachesmentioning
confidence: 91%
“…55 Two prospective cohort studies and one cross-sectional study have shown that BMI can independently predict acute pain intensity or severity after knee arthroplasty. 30,45,49 Moreover, BMI was reported to be a significant risk factor for moderate-to-severe acute pain after open radical gastrectomy, 56 thoracoscopic surgery, 29 and breast cancer surgery. 38 One retrospective study and one cross-section study have noted the correlation between BMI and APSP.…”
Section: Obesitymentioning
confidence: 99%
“…[1] The number of abdominal surgeries is increasing, especially in East Asian countries such as Japan due to the large number of cancer patients. [2] The most common complication following abdominal procedures is pain centered around the surgical wound, and many reports regarding its intensity, changes, associations with cancer site, [3,4] surgical technique, [5] and long-term duration have been published. [6] Various treatment strategies for postoperative pain have been investigated including reducing the release of inflammatory cytokines through preoperative nutritional therapy, [7] intraoperative anesthetic administration, [8] and application of postoperative analgesics, [9,10] among others.…”
Section: Introductionmentioning
confidence: 99%